2015
DOI: 10.1053/j.semperi.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Interpregnancy care

Abstract: The aim of interconception care is to provide women who have had a prior adverse pregnancy outcome with optimal care in order to reduce risks that may affect the woman׳s health and any future birth she may choose to have. National recommendations call for action, and evidence supports specific clinical interventions. The need for interconception care is documented in national and state survey and surveillance data. Chronic diseases and behavioral risks affect the health of millions of U.S. women of childbearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Many of these problems are associated with an increased risk of complications in subsequent pregnancies; for example, previous histories of pre‐eclampsia and postpartum haemorrhage have been shown to be associated with future morbidity 20, 29, 30. It has been suggested that inter‐pregnancy care targeted at the management of hypertension and diabetes could improve future pregnancy outcomes 31. However, research evaluating the impact on future outcome is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these problems are associated with an increased risk of complications in subsequent pregnancies; for example, previous histories of pre‐eclampsia and postpartum haemorrhage have been shown to be associated with future morbidity 20, 29, 30. It has been suggested that inter‐pregnancy care targeted at the management of hypertension and diabetes could improve future pregnancy outcomes 31. However, research evaluating the impact on future outcome is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that preconceptionally delivered biomedical, psychosocial, and behavioral interventions are effective [1, 11, 18]. Furthermore, recent studies have shown a high prevalence of risk factors in the preconception and interconception period both in the Netherlands [21], as well as in the U.S. [12]. Despite consensus on the importance of preconception and interconception care, this care is still rarely delivered.…”
Section: Introductionmentioning
confidence: 99%
“…This possibility is especially relevant to interconception care. Interconception care covers the period between pregnancies and is particularly valuable for women who have experienced an adverse pregnancy outcome [12]. Most women who give birth receive some form of perinatal care, postpartum care, and pediatric care for their newborn child.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postpartum care is recommended to assess women's recovery from pregnancy, need for contraception, success with lactation, risk of postpartum depression, and ongoing need for care of medical conditions identified during pregnancy, such as gestational diabetes [1]. Postpartum care and postpartum contraception play a critical role in ensuring mothers have adequate time to recover from delivery before conceiving a subsequent pregnancy.…”
Section: Introductionmentioning
confidence: 99%